Intermittent estuaries deserve global attention as vulnerable and vital ecosystems - Danial Khojasteh; Shivanesh Rao; Sarah McSweeney; Raimundo Ibaceta; Robert J. Nicholls; Jon French; William Glamore; John L. Largier; Janine Adams; Michael G. Hughes; Michael Barry; Hannah E. Power; et al. (Communications Earth & Environment)
Abstract Intermittently closed estuaries provide important ecosystem services but are often overlooked in coastal and catchment research and management. These estuaries are highly vulnerable to human and climate disturbances due to their episodic closure to the ocean, yet remain understudied. This study maps 2245 intermittent estuaries globally, whose catchments currently support 55 million people, with projections of up to 101 million by 2100. Analysis of three decades of scholarly literature revealed that only 7% of these estuaries have been studied. Research on intermittent estuaries comprises 0.5% of all estuarine literature, despite representing 4–5% of estuaries globally. Major research gaps exist in Asia, South America, and Africa—regions with large, vulnerable populations. Over 90% of research on intermittent estuaries is conducted in (southern) Africa, Oceania, and North America, with most studies focusing on local physico-chemical and eco-hydro-geomorphological processes. This assessment underscores the need to expand research priorities to include ecosystem services, climate and human disturbances, and management, with greater international collaboration and leadership from intergovernmental organisations.